2017
DOI: 10.1563/aaid-joi-16-00086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Alteration of Occlusal Distribution in Unilateral Free-End and Intermediate Missing Cases

Abstract: The present study aimed to evaluate the effect of implant prostheses on the occlusal force and area as well as the distribution of occlusal loading in unilateral free-end and intermediate missing cases. Fourteen healthy subjects (7 free-end missing cases in the first and second molars and 7 intermediate missing cases in the first molar region) were included. Six months after the implant prosthesis was placed, an occlusal evaluation was performed with or without the implant superstructure by using Dental Presca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…While during strong chewing, the force on the implant and adjacent tooth was comparable with no gap between them. So, the force on the implant and adjacent tooth had finally become comparable, but if the gap is more than 20um, the load distribution on the adjacent tooth would be more than that on the implant (10) .…”
Section: Discussionmentioning
confidence: 99%
“…While during strong chewing, the force on the implant and adjacent tooth was comparable with no gap between them. So, the force on the implant and adjacent tooth had finally become comparable, but if the gap is more than 20um, the load distribution on the adjacent tooth would be more than that on the implant (10) .…”
Section: Discussionmentioning
confidence: 99%
“…When these teeth are missing, the maximum biting force shifts forward. Studies (Kon et al, 2017) have shown that restoration of free-end posterior teeth can reduce the occlusal load of the remaining natural teeth.…”
Section: Introductionmentioning
confidence: 99%
“…When these teeth are missing, the maximum biting force shifts forward. Studies ( Kon et al, 2017 ) have shown that restoration of free-end posterior teeth can reduce the occlusal load of the remaining natural teeth. Therefore, implant restoration of the free-end missing posterior teeth may protect the adjacent natural teeth.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is very prominent in rural areas and even some third and fourth cities (Jiang W, Zhang J, Lv X, 2018). The disadvantage is that oral training is only a task rather than teacher-student and active communication within the heart (Kon K, Shiota M, Sakuyama A, 2017). Part of the teaching model introduced foreign teachers, which solved a teacher's problem to a certain extent but did not promptly guide and encourage students, which to some extent caused resources to be fully occupied by only a small number of highly motivated students and cannot make oral English training a full-…”
Section: Introductionmentioning
confidence: 99%